2018
DOI: 10.1186/s13705-018-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and risks for renewable energy developments in mountain regions: a case of a pilot photovoltaic project in the Swiss Alps

Abstract: Background: When renewable policies are in place, the mismatch between policy targets and lack of technology diffusion indicates a gap between codifying a policy and implementing it. In Switzerland, photovoltaic (PV) electricity is seen to play a major role in the future. Stakeholders' opinions in the implementation of photovoltaic projects may block or delay the achievement of renewable policy goals. This paper explores the question: which are the main drivers and risks perceived by stakeholders at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Public opinion may be against such projects, especially since many of the water bodies in our sample are popular tourist destinations. Previous research on the risks of developing photovoltaic projects in the Swiss alps has found that project acceptance relies heavily on contributions to the local economy, with transparent and regular information flows between stakeholders as a key driver of project approval ( Díaz and Van Vliet, 2018 ) – the study also found that the high complexity of administrative processes related to developing new renewable projects pose a significant implementation risk. Given the existing local relationships and permits held by hydropower facilities, the path of least resistance for implementing high-altitude floating solar is likely to be through associated hydro operators.…”
Section: Discussionmentioning
confidence: 89%
“…Public opinion may be against such projects, especially since many of the water bodies in our sample are popular tourist destinations. Previous research on the risks of developing photovoltaic projects in the Swiss alps has found that project acceptance relies heavily on contributions to the local economy, with transparent and regular information flows between stakeholders as a key driver of project approval ( Díaz and Van Vliet, 2018 ) – the study also found that the high complexity of administrative processes related to developing new renewable projects pose a significant implementation risk. Given the existing local relationships and permits held by hydropower facilities, the path of least resistance for implementing high-altitude floating solar is likely to be through associated hydro operators.…”
Section: Discussionmentioning
confidence: 89%
“…Q is the most adequate technique for understanding subjectivity and leads to more correct policy measures. Different perspectives on photovoltaic energy have also been addressed [37][38][39][40][41]. Previous, solely quantitative research on planning photovoltaic infrastructure led to strictly technical outcomes, where experts' subjective opinions had not been taken into consideration.…”
Section: Q-methodology and Subjective Perceptions In The Field Of Energymentioning
confidence: 99%
“…Second, this study would help identify lessons learned from these strategies efforts and also identify constraints that may need to be addressed for wind energy development. It adds to planning approaches, when there is a missing evolutive linkage between overall energy targets and actual implementation at local level [6][7][8]26,27,59 for solar energy].…”
Section: Motivation and Research Questionsmentioning
confidence: 99%